Association of Candida Species with Novel SARS-CoV-2 and Biomarkers for Fungal Premalignant Oral Lesions - Aslam, Sidra; Sarah Ghafoor (Journal of the Pakistan Medical Association, 2022)
Oral fungal infections can be caused by certain species of fungi among which candida albicans is the most implicated. Oral candidiasis is correlated with multiple conditions, such as coronavirus disease-2019, oral leukoplakia and oral erythroplakia. Tenascin is a glycoprotein and is present at the site of tissue injury and chronic inflammation, and tends to be over-expressed in cases of malignancy. Matrix metalloproteinase-9 belongs to a family of zinc-dependent endopeptidases and is involved in the degradation of extracellular matrix, leading to tissue invasion and metastasis. The current narrative review was planned to shed light on the fungal co-infections of coronavirus disease-2019 and molecular mechanisms of matrix metalloproteinase-9 and tenascin involved in the pathogenesis of fungus-associated oral leukoplakia and oral erythroplakia. Key Words: Oral, fungal, COVID-19, Tenascin, MMP-9.